An in vitro comparative study on the antimicrobial effects of bioglass 45S5 vs. calcium hydroxide on Enterococcus faecalis - Mehrvarzfar, Payman; Akhavan, Hengameh; Rastgarian, Hossein; Mohammadzade Akhlagi, Nahid; Soleymanpour, Reza; Ahmadi, Anahid (Iranian Endodontic Journal, 2011)
INTRODUCTION: An ideal intracanal medicament should be able to eliminate any remaining intracanal microorganism. The aim of this study was to compare the antimicrobial effects of Bioglass 45S5 with calcium hydroxide on Enterococcus (E) faecalis in-vitro. MATERIALS & METHODS: Direct exposure test (DET) was used to evaluate the antimicrobial effect of Bioglass 45S5, calcium hydroxide and normal saline (control group) on 80 paper cones contaminated with E. faecalis suspension. All samples were aseptically transferred into BHI culture medium to quantify microbial concentration in periods of 1, 24, 48 and 72 hours. Turbidity of the culture medium was measured via optical density (OPD) method with a spectrophotometer (wavelength=540nm). Results were then analysed statistically using student t-test. RESULTS: Mean difference of optical density between Bioglass 45S5 and calcium hydroxide appeared insignificant within 1 hour of the test period (P>0.05); however calcium hydroxide showed significantly greater antimicrobial properties after 24 hours (P<0.05). Antimicrobial effect of both materials displayed significant increases with time. CONCLUSION: Although both Bioglass 45S5 and calcium hydroxide exhibited antimicrobial effects against E. faecalis, neither attained complete eradication of bacteria. However, calcium hydroxide seemed to have superior disinfecting effect.